First data about fungal diversity of the “Trekhizbenskyi Step” division of the Luhansk Nature Reserve - Ordynets, O.; Akulov, O.; Helleman, Stip (Херсонський державний університет, 2013)
One hundred and fifty fungal species were revealed by us in the “Trekhizbenskyi Step” division of the Luhansk Nature Reserve. Of them, 52 species are those belonging to Ascomycota and 98 to Basidiomycota. All the species are reported from the research area for the first time. Eleven species are recorded in Ukraine for the first time. The records of Perrotia cf. succina (W. Phillips) Dennis and Streptotinia caulophylli M.E. Elliott are new to Europe. Phaeosphaeria sp. collected from Chamaecytisus ruthenicus (Fisch. ex Vorosch.) Klask. is supposed to be a new species. Detailed morphological descriptions and illustrations are provided both for taxonomically significant records and the species that are firstly revealed in Ukraine.
Ординець О., Акулов О., Хеллеман С. Перші відомості про різноманіття грибів відділення «Трьохізбенський степ» Луганського природного заповідника
Ордынец А., Акулов А., Хеллеман С. Первые сведения о разнообразии грибов отделения «Трехизбенская степь» Луганского природного заповедника
Keywords: Ascomycota; Basidiomycota; Perrotia; Phaeosphaeria; Streptotinia; diversity; distribution; new records; sandy steppe; Ukraine